Re: Association between endothelin receptor B nonsynonymous variants and melanoma risk - Thirumaran, Ranjit Kumar; Figl, Adina; Ugurel, Selma; Hemminki, Kari; Schadendorf, Dirk; Kumar, Rajiv (Journal of the National Cancer Institute, 2006)
The known genetic risk factors for malignant melanoma, besides CDKN2A and CDK4 mutations, include variant alleles of the melanocortin-1 receptor (MC1R) gene ( 1 ) . Recently, Soufir et al. ( 2 ) in a study that was based on 137 malignant melanoma patients and 131 ethnically matched control subjects reported an association between nonsynonymous variants in the endothelin receptor B (EDNRB) gene and increased risk of melanoma. They reported six nonsynonymous EDNRB variants in 15 patients compared with two variants in four control subjects. EDNRB promotes migration and proliferation of melanocyte precursors during embryonic development ( 3 ) . The overexpression of EDNRB in most human melanomas and the shrinkage of tumors in immunocompromised mice and induction of apoptosis upon inhibition of EDNRB suggest a role in disease progression ( 4 , 5 ) . Mutations in the gene are associated with several genetic disorders. The most common variant detected by Soufir et al. in 12 melanoma patients and three control subjects, S305N, has previously been reported in Hirschsprung disease ( 2 , 6 ) .
Gesehen am 05.02.2021